PENGARUH PENERAPAN PSAK 72 DAN PSAK 73 TERHADAP KINERJA KEUANGAN - Lestari, Mei Lin Teja Dwi (Jurnal Akuntansi Kontemporer, 2023)
Research Purposes. The purpose of this study is to determine the impact of the adoption of PSAK 72 and PSAK 73 on the financial performance of IDX non-financial companies in 2019-2021.Research Methods. As the source of the data extracted is secondary data on financial statements of non-financial companies listed on the Indonesian Stock Exchange in 2019-2021, this study uses quantitative methods.Research Results and Findings. Based on the test results, it shows that the value of the independent variables PSAK 72 and PSAK 73 on the company's financial performance is insignificant. The results of this study found that PSAK 73 has no significant effect on financial performance.  For the control variable, the company's size showed a sig value close to significant, namely 0.065 to NPM's financial performance and 0.092 to ROE's financial performance. Industrial type control variables show insignificant value to financial performance. As a result of the analysis and discussion on the impact of the adoption of PSAK 72 and PSAK 73 on financial performance, it can be concluded that the adoption of PSAK 72 and PSAK 73 will not affect the financial performance of the company. The study results open opportunities for further research on the relevance of changes in accounting standards on financial performance.